What Do Explore Employee Retention Factors: The Mediating Role of Job Satisfaction - Alden Nelson; Aisyah Fitriana (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
This research examines various factors that influence employee retention, with an emphasis on job satisfaction as a mediating. This research applied quantitative research and a non-probability sampling approach. The data were analyzed using Smart PLS 3.0. The research sample was conducted on employees in the manufacturing industry in Batam with a total of 320 respondents. The results found that leadership, compensation, and work environment influence job satisfaction, but these three variables do not influence employee retention. At the same time, the indirect effects showed that job satisfaction as a full mediation influences the relationship between leadership, compensation, and work environment on employee retention. Today, employee retention has become increasingly urgent in a dynamic job market, where low retention rates not only strain organizational resources but also jeopardize continuity, innovation and overall business performance, thereby underscoring the importance of effective retention strategies. This research showed how the organization carries out employee retention strategies and can be used as evaluation material and guidance for the industry in increasing employee retention within the organization.